2021
DOI: 10.1002/jez.b.23036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of constant and fluctuating temperature on the intrapuparial development of Sarcophaga argyrostoma (Robineau‐Desvoidy, 1830; Diptera: Sarcophagidae)

Abstract: This study aimes to investigate the effect of constant and fluctuating temperatures on starting times of developmental periods of insect species. For this purpose, Sarcophaga (Liopygia) argyrostoma (Robineau‐Desvoidy, 1830), a forensically important species has been chosen. Whether the constant (25°C) and fluctuating (25.2°C averaged over natural conditions) temperatures would make a difference on the timing of intrapuparial development of this species was investigated. First larval instars were placed in rear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Another study also showed a longer development time for Aldrichina grahami under fluctuating temperatures, in which a greater impact on Aldrichina grahami at low temperature periods than at high temperature periods was suspected [23]. Sert et al [36] observed a longer total intrapuparial development of Sarcophaga argyrostoma under fluctuating temperature conditions compared to constant temperatures, but this retardation is not statistically significant. Colinet et al [37] considered that the effect of fluctuating temperatures depends on the thermal mean and its closeness to the developmental thresholds.…”
Section: Development Of C Vicinamentioning
confidence: 95%
“…Another study also showed a longer development time for Aldrichina grahami under fluctuating temperatures, in which a greater impact on Aldrichina grahami at low temperature periods than at high temperature periods was suspected [23]. Sert et al [36] observed a longer total intrapuparial development of Sarcophaga argyrostoma under fluctuating temperature conditions compared to constant temperatures, but this retardation is not statistically significant. Colinet et al [37] considered that the effect of fluctuating temperatures depends on the thermal mean and its closeness to the developmental thresholds.…”
Section: Development Of C Vicinamentioning
confidence: 95%
“…Sert et al (2021) evaluated Sarcophaga argyrostoma Robineau‐Desvoidy, 1830 every hour at the constant temperature of 25°C under laboratory conditions and at 25.2°C with natural temperature fluctuation conditions. Adult emergence occurred in 289.5 h (~12 days) at 25°C and 319 h (~13 days) at 25.2°C—intervals similar to that of 272 h (~11 days) at 27°C for S .…”
Section: Discussionmentioning
confidence: 99%
“…Martín-Vega et al (2016) underscored the significance of utilizing correct nomenclature for the stages and events occurring throughout intrapuparial development. The authors emphasized the importance of correctly understanding and interpreting the morphological characteristics that emerge throughout these periods.The study conducted bySert et al (2021) was the first to focus on intrapuparial development to assess pupae at 1-h intervals, thereby contributing to more detailed data. A total of 23 periods of intrapuparial development were presented, encompassing the events, stages and morphological characteristics associated with each pupal age.…”
mentioning
confidence: 99%
“…They found that A. grahami developed slowly under changing temperatures ranging from 6 to 20 • C, according to the natural meteorological conditions, than under stable temperatures ranging from 8 to 36 • C. These correlated with our findings in the present study. Sert et al [72] analyzed the impact of fixed and changing temperatures on the post-feeding time of S. argyrostoma (Diptera: Sarcophagidae) and found a similar intrapuparial development with a non-significant difference between adult emergence times at fixed temperatures (25 • C) and variable temperature conditions. Although this result concerned exclusively the intrapuparial stage, it was similar to the observation made on the growth time of S. crassipalpis under variable temperatures vs. 25 • C in the current research.…”
Section: Discussionmentioning
confidence: 99%